PENGARUH LINGKUNGAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KARIYAWAN - Niko Ruslan; Rafael Tomi (MARHALADO : Jurnal Pengabdian kepada Masyarakat, 2023)
The main task of Bank Jatim is to participate in encouraging the growth of regional economic potential through its participation in developing small and medium credit business sectors in order to obtain optimal profits. Its main activities are collecting and distributing funds and providing other banking services. Until 2019 Bank Jatim has a total of 1,706 operational services, both conventional and sharia services. Bank Jatim currently has e-banking services such as ATM, SMS banking, Internet Banking, Mobile Banking and most recently the jatimcode feature to make it easy for customers to transact wherever and whenever they are. Apart from collaborating with the ATM Bersama network and the Prima network, Bank Jatim has also joined the National Payment Gateway (GPN), which means that bankjatim ATM cards can be used at all ATMs and merchants in Indonesia bearing the ATM Bersama, Prima and GPN logos without any fees.